1991
DOI: 10.1111/j.1348-0421.1991.tb01545.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Subpopulations and Cytokine Production in Paracoccidioidomycosis Patients

Abstract: Despite the postulated role of the immune system in the control of the infection by Paracoccidioides brasiliensis, only a few studies have addressed this point in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
1
7

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 14 publications
4
30
1
7
Order By: Relevance
“…Magnification, ϫ200 for figures A, B, C, F, and ϫ400 for E. the mobilization of DC into the peripheral circulation and tissues (30). We did not confirm that the ratio of CD4-CD8 was decreased in patients with PCM (31). The latter results may reflect the fact that patients studied here exhibited the chronic form of disease.…”
Section: Discussioncontrasting
confidence: 54%
“…Magnification, ϫ200 for figures A, B, C, F, and ϫ400 for E. the mobilization of DC into the peripheral circulation and tissues (30). We did not confirm that the ratio of CD4-CD8 was decreased in patients with PCM (31). The latter results may reflect the fact that patients studied here exhibited the chronic form of disease.…”
Section: Discussioncontrasting
confidence: 54%
“…In T-cell subpopulations in the peripheral blood of patients with acute or chronic forms of PCM, a significant fall in the CD4/CD8 T-cell ratio was detected (2,30). Some authors observed decreased numbers of CD4 ϩ and CD8 ϩ T cells (30), whereas others reported a decrease only in the CD4 ϩ subset (2).…”
Section: Discussionmentioning
confidence: 96%
“…Another study showed a decrease in CD4 ϩ lymphocyte levels in patients with fungal infections (5). An opposite trend (consisting of an increase in CD4 ϩ lymphocyte levels) was reported for patients with meningitis infection, however, whereas Staphylococcus infection caused a reduction in the proportion of CD11 ϩ and CD8 ϩ lymphocytes (2).…”
Section: Discussionmentioning
confidence: 99%